Pengaruh Pertimbangan Pasar Kerja, Self Efficacy, Pengetahuan Perpajakan, dan Personalitas terhadap Minat Karir Mahasiswa Akuntansi Menjadi Konsultan Pajak - sari, Wulan; Herawansyah, Herawansyah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to examine the influence of labor market considerations, self-efficacy, tax knowledge, and personality on accounting students' interest in pursuing a career as tax consultants within the LLDIKTI Region II. A quantitative approach was employed using a survey method. Data were collected through an online questionnaire (Google Forms) distributed to 202 students from four public universities, with respondents selected using purposive sampling. The results of multiple linear regression analysis show that all four independent variables have a positive and significant influence on students’ interest. The significance values for each variable were below 0.05, and the adjusted R² value was 0.513, indicating that 51.3% of the variation in students' interest in becoming tax consultants can be explained by these variables. It is hoped that these findings can contribute to increasing students' interest in pursuing careers as tax consultants. Future research could strengthen this model by considering additional factors outside the scope of this study that may influence accounting students' career choices.